2018
DOI: 10.4103/jde.jde_10_18
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Upper Gastrointestinal Endoscopy and Prevalence of Helicobacter Pylori Infection in Dyspeptic Type 2 Diabetes Mellitus Patients

Abstract: Introduction: Multisystem involvement is a norm in Type 2 diabetes mellitus (T2DM). Dyspepsia is a common gastrointestinal (GI) tract symptom in people with diabetes. We aimed to study the esophageal, gastric, and duodenal mucosal changes; presence of Helicobacter pylori (HP) infection; and its significance in dyspeptic diabetes patients. Materials and Methods: A prospective observational study done on 287 patients (147 patient with diabetes and 140 nondiabetic controls) with dyspepsia of more than 6 months du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Although, there were differences in endoscopic findings between the groups, it was not statistically significant [22]. On the other hand, Vasihnav et al found that the presence of pangastritis and bulbite was higher in patients with DM, compared to non-diabetic patients, and the presence of HP was higher [23]. In our study, there was no significant difference between endoscopic findings in comparison with HbA 1c levels in patients with diabetes.…”
Section: Discussioncontrasting
confidence: 72%
“…Although, there were differences in endoscopic findings between the groups, it was not statistically significant [22]. On the other hand, Vasihnav et al found that the presence of pangastritis and bulbite was higher in patients with DM, compared to non-diabetic patients, and the presence of HP was higher [23]. In our study, there was no significant difference between endoscopic findings in comparison with HbA 1c levels in patients with diabetes.…”
Section: Discussioncontrasting
confidence: 72%
“…We explained that diabetic patients are prone and correlate to chronic H. pylori infections because evidence indicates that diabetes may be accompanied by H. pylori infection, which chronic and insulin-resistant inflammation may increase the risk for T2DM. In addition, gastritis resulting from H. pylori may potentially affect gut-related hormones and inflammatory cytokines [30]. This relationship, some reasons can be considered to discuss it, which are summarized in the following: First, diabetes causes impairment in the function of cellular and humoral immunity, which also increases the individual's sensitivity to H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…In an Indian study done in 2018 by Vaishnav et al . [ 24 ] it was concluded that dyspepsia was common in type 2 diabetes, however, there was no difference in the type of dyspeptic symptoms between diabetics and non-diabetics.…”
Section: Discussionmentioning
confidence: 99%